Analysis of Ownership Network in the Iranian Stock Markets - Reza Taghizadeh (Ph.D) (Shahid Bahonar University of Kerman, 2018)
The analysis of stock market is crucial in predicting future events, and the network analysis is one of the newest methods in the analysis of stock market. In the quantitative science literature, network analysis is new concept for macro viewing of the whole market. Quantifying the relationship between different units is the favorite issue in scientific studies in understanding complex systems. The purpose of this research is to analyze the ownership network of the companies in the Iranian stock markets. The data in the years 2011-2016 was collected and analyzed, using softwares PreMap and UCINET. Results indicated that the class structure overcomes corporates’ relations, and some companies, in comparison with others, are in better position. This better position provides faster access to the available resources. Also, for the companies in better position, the ability in access to information through the cluster of network members has increased. Furthermore, such an advantage has enhanced their power of influence in the stock market. Hence, it can be claimed these companies are key actors in the governing structure of the Iranian stock market.